A multimodality network platform for oncologic solution. (September 2016) - Di Rosa, F.; Costa, R.; Politi, G.; Sardina, D.
Abstract : Introduction: Two facilities, located in different geographical areas and related to a single Radiotherapy Department, need a massive storage of multimodal DICOM images. A network connection is required in order to share all clinical, physical and dosimetric information. Purpose: We design and implement a server infrastructure to perform a real time connection for the full management of a Radiotherapy Department. Materials and methods: We developed a server architecture dedicated to radiotherapy requirements based on an advanced DICOM forwarding rules: RTPACS. The combination of this system with an advanced DICOM viewer assures a full support of DICOM standard extension. The use of a DICOM server, embedded with programmable SQL databases, offers all solutions to satisfy the requirements for a long-term storage allowing the clinical plan evaluation free by TPS vendor. Results: RTPACS provides easy access to the single patient waiting list and a multidisciplinary and multicenter study of a same patient: a treatment can be planned, valued, approved and delivered independently in both facilities. Such system ensures a continuative service avoiding treatment interruptions caused by machine maintenance or downtime. Moreover, RTPACS constitutes a tool to manage, compare and storage the quality controls results performed by images. Conclusion: A network implementation joining two far facilities of the same Department answers to the needs and cares of the oncologic patient. It represents an innovative, easy and affordable solution that provides a service we cannot find in our territorial area. A unique radiotherapy data management permits a better organization of human resources. Disclosure: Authors disclose any relationship that may prejudice their presentation.